Evaluación de la infraestructura y planta turística para la mejora del desarrollo turístico de la parroquia Cojimíes-Pedernales post terremoto - Chamorro Cevallos, Marian Jahel (2021)
The objective of the project is to evaluate the infrastructure and tourism plant to improve the tourism development of the Cojimíes-Pedernales parish post-earthquake, to help capture problems in tourist establishments, in order to strengthen and improve services to preserve and increase the demand and therefore the economy. We rely on a three-phase methodological design: carry out a current diagnosis of the infrastructure; We carried out a bibliographic review, cadastre, damage statistics, direct observation and interviews, which helped to obtain 2 health centers, 7 restaurants and 29 accommodations with permits and easy access since they are located in the downtown area. Cojimíes has roads in good condition and transport of buses and motorcycle taxis from Pedernales to the parish. II phase; Selection of criteria where a bibliographic review was used, Delphi method, synthesis matrix, observation, field work, interview, multivariate analysis, analytical-synthetic method, descriptive method, mentioning that these tools helped to establish appropriate indicators to evaluate, they were carried out surveys of these establishments and deficiencies were found. Phase III consisted of identifying strategies to improve tourism development, a strategic analysis was carried out in which the SWOT matrix was used, this tool allowed to know the status of the establishments, once the infrastructure was evaluated, the main shortcomings were identified, for which were selected the 4 most punctuated weaknesses and intervention strategies were developed to overcome problems, this will help to improve tourism services and therefore socioeconomic development.